Indonesia’s Soft Power Diplomacy Agenda in Supporting National Interests - I Kadek Andre Nuaba (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
In the context of global geopolitical tensions and the rising use of hard power, the effectiveness of soft power has been questioned. However, Indonesia remains committed to leveraging soft power as a tool in diplomacy to achieve its national interests. This study aims to examine Indonesia's national interests through the soft power agendas pursued by the Ministry of Foreign Affairs and assess their implementation through the pillars of soft power diplomacy. Using a descriptive qualitative method with a literature review approach, this research concludes that Indonesia's soft power diplomacy agenda aims to build a positive image as a democratic, moderate, and progressive nation. These national interests are realized through the four pillars of soft power diplomacy: politics and national values, economy and tourism, socio-culture, and the roles of actors in diplomacy. Despite the inherent limitations of soft power, Indonesia continues to rely on other instruments to support the creation of the desired positive image.